Gerenciamento de resíduos de serviços de saúde durante a pandemia do Covid-19: uma investigação no Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
On March 11, 2020, the World Health Organization (WHO) declared a pandemic state, the entire world population was surprised with the arrival of the new coronavirus, and with it came the responsibilities and care for individual and collective protection. The pandemic brought challenges that go beyond health care, it also brought changes in personal relationships, new habits and changes in both domestic and hospital spaces. With the increased use of personal protective equipment (PPE), such as masks and hygiene products, in addition to the large number of infected and hospitalized people due to SARS-CoV-2, a great growth in solid waste generation was triggered. The correct management of solid waste, regardless of its classification, is a crucial element for the well-being of human health and the environment; and with that; it is of utmost importance that this process is effective; even with the arrival of the pandemic. The aim of this study is to survey information in scientific, legislative and information databases in general, which address the theme "health care waste management in the midst of the covid-19 pandemic period in Brazil", and reviews them in a narrative way. It was observed that, during the pandemic period, the Ministry of Health, the National Agency of Sanitary Monitoring and other institutions were the main organizations responsible for providing guidance on the correct management of waste from health services according to the WHO. It is correct to state that the management of hospital waste and other sources of RSS will follow correctly, if the guidelines of the Health Services Waste Management Plan of each institution are followed, together with the measures passed on by the organizations.
Keywords: Resíduos de serviços de saúde; Gerenciamento; Pandemia do covid-19; CNPQ:: Ciências Biológicas